The Fiduciary Guarantee Revolution: Optimizing Trademark Rights to Accelerate Banking Financing in Indonesia - Moh. Fadlan Wahidji; Nur Mohamad Kasim; Weny Almoravid Dungga (Fakultas Syariah INSURI Ponorogo, 2026)
This study examines the legal and implementation challenges of using trademark rights as fiduciary guarantees to accelerate bank financing in Indonesia. Employing normative legal research with statutory and conceptual approaches, the analysis covers the Civil Code, Fiduciary Guarantee Law, Trademark Law, Copyright Law, Patent Law, and Creative Economy Law. The findings reveal that trademark rights, classified as intangible movable assets under the Civil Code, possess a sound juridical foundation for fiduciary security. However, there is normative disharmony: the Trademark Law remains silent on fiduciary transfers, while copyright and patent laws explicitly authorize them. The Creative Economy Law resolves this ambiguity by expressly permitting trademarks as fiduciary collateral. Despite this normative progress, implementation in Indonesian banking practice remains unrealized due to fundamental obstacles, including complex valuation, the absence of specialized institutions and standardized methodologies, prudential concerns, and a lack of uniform operational protocols. Addressing these challenges requires coordinated efforts among the government, financial authorities, and banks to develop valuation infrastructure, regulatory guidance, and internal banking capacity.